Electronic Device Selection in Industrial Products and Machinery Industry: Comparative Analysis with Ocra and Maut Method - Ozdagoglu, Askin; Çirkin, Elif (International Journal of Contemporary Economics and Administrative Sciences, 2019)
The diversity and abundance of product alternatives lead to vagueness on decisions related to procurement, production, and R & D management processes along with other decisions taken within the company and render purchasing, production and R&D decision processes, much more effortful. As choosing appropriate and effective decisions within purchasing, production, R&D, and all other departments are of great importance in today’s competitive business environment, firms are strongly encouraged to concentrate on their decision processes. Within the scope of this study, the purchase decisions of electronic device alternatives are being analysed in industrial products and machinery industry with OCRA method. The importance levels of evaluation criteria for the purchase are obtained out of 100 points. These importance levels are then being used in OCRA method in an attempt to evaluate various electronic device alternatives. In order to scrutinize the results, it can be said that the same data set is compatible with MAUT, which is another multi-criteria decision making method. Information regarding the evaluation criteria as well as alternatives of electronic device has been gathered through focus group study that includes marketing and purchasing managers. The results provide useful information for the sector.